1979
DOI: 10.1111/j.1432-1033.1979.tb13083.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Biosynthesis Is not Necessary for Initiation of DNA Replication

Abstract: Synthesis of mature 28-S ribosomal RNA and 60-S ribosomal subunits is inhibited in baby hamster kidney (BHK) cell line ts 422E at non-permissive temperature (39 "C). This leads to a 66 decrease of total ribosomes per cell, a marked imbalance between the large and small ribosomal subunits in the cytoplasm and a decrease of cells per dish after prolonged culture at 39 "C. However, inhibition of ribosome synthesis does not affect progression of cells through the GI period of the cell division cycle, the length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, previous studies with mammalian cells indicate that interference with ribosome biogenesis by other means can also inhibit cell proliferation. For example, the ts422E temperature-sensitive mutant of the Syrian hamster cell line BHK21 that is unable to produce mature 28S rRNA and 60S ribosome subunits was rapidly growth arrested at the nonpermissive temperature (38,61); the nature of this growth defect, however, has not been clearly defined (20,41). Antisense-mediated inhibition of the nucleolar protein p120, a human homolog of the yeast Nop2p that is implicated in biosynthesis of the large ribosome subunit, arrested human lymphocytes in G 1 (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies with mammalian cells indicate that interference with ribosome biogenesis by other means can also inhibit cell proliferation. For example, the ts422E temperature-sensitive mutant of the Syrian hamster cell line BHK21 that is unable to produce mature 28S rRNA and 60S ribosome subunits was rapidly growth arrested at the nonpermissive temperature (38,61); the nature of this growth defect, however, has not been clearly defined (20,41). Antisense-mediated inhibition of the nucleolar protein p120, a human homolog of the yeast Nop2p that is implicated in biosynthesis of the large ribosome subunit, arrested human lymphocytes in G 1 (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, this reactivation and expansion of the protein-synthesizing machinery is actually not needed for G O cells to wake up and transit G r Thus, reactivating a temperaturesensitive avian sarcoma virus's oncogenie/mitogenis pp60 ..... tyrosine • PK product or a temperature-sensitive Kirsten sarcoma virus's oncogenic/ mitogenic 21kDa K-RAS Gc~(or N,)-like protein causes their serum-deprived G O NRK rat kidney cell hosts to transit G 1, replicate DNA and ultimately divide without stimulating RNA or protein synthesis [277][278][279]. Moreover, mutant BHK hamster cells that cannot process the 45S ribosomal RNA precursor and make ribosomes at certain non-permissive temperatures can be stimulated by serum to transit G~ phase and replicate DNA at these same restrictive temperatures [280,281]. However, it is the stimulation of only one or a few master CDC genes (e.g., c-rnyc?)…”
Section: Cultured Cell Linesmentioning
confidence: 99%
“…The absence of a strong correlation between cell size and the time of entry into S phase is in conformity with the published reports. A number of investigators have previously shown that initiation of DNA synthesis can occur in mammalian cells without a concomitant accumulation of RNA (Grummt et al, 1979;Pochron et al, 1980;Mora et al, 1980) or protein (Ronning et al, 1981) or increase in cell size (Zetterberg and Engstrom, 1981;Zetterberg et al, 1982). From our data it is clear that slowing down the chromosome replication cycle does result in a shortening of GI period but only to a limited extent.…”
Section: Discussionmentioning
confidence: 99%